Effect of lactose-free UHT milk macromolecules on the colligative property of cryometry - Santomauro, Rafael Alves; Papi, Lucas Lamas; Almeida, Augusto Heitor Pedro de; Mariano, Gabriel Henrique Gomes; Possebon, Fábio Sossai; Pereira, Juliano Gonçalves; Rossi, Gabriel Augusto Marques; Martins, Otávio Augusto (Food Science and Technology, 2025)
Ultra-high-temperature milk in Brazil is marketed in categories based on fat content: whole, semi-skimmed, and skimmed. Additionally, there are options for consumers with some degree of lactose intolerance, classified as “lactose-free” or “low-lactose” according to lactose concentration. Cryometry is a colligative property for detecting milk fraud through the addition of water and/or reconstituted components. This study aimed to evaluate the effect of macromolecules in lactose-free ultra-high-temperature milk on the colligative property of cryometry. Physicochemical characteristics of ultra-high-temperature milk (whole, semi-skimmed, skimmed, and lactose-free) were analyzed, including protein, carbohydrate, and lipid contents; density; total and non-fat solids; minerals; and cryometry (or cryoscopy). The lactose-free milk presented higher protein (3.30 g/100 g ± 0.13 g/100 g), carbohydrate (4.97 g/100 g ± 0.20 g/100 g), and mineral content (0.72 g/100 g ± 0.04 g/100 g) and a lower freezing point (−0.569 °H ± 0.021 °H). Lactose hydrolysis by lactase increases the number of dissolved solutes, reducing the freezing point. Therefore, it plays a significant role in increasing the number of dissolved solutes contributing to the reduction of the cryoscopic point compared to other categories.